First record of the beetle Postelichus musgravei (Hinton, 1935) for Nuevo León, Mexico, with a checklist of species and a key to the genera of the family Dryopidae (Coleoptera: Byrrhoidea) in Mexico: Dryopidae of Mexico - Jordán Hernández, María; de Luna, Manuel; Cuéllar-Rodríguez, Gerardo (Instituto de Ecología, A.C., 2023)
The aquatic long toed beetle Postelichus musgravei (Hinton, 1935) (Coleoptera: Byrrhoidea: Dryopidae) is registered for the state of Nuevo León, Mexico, this being the first record of the family Dryopidae for this state, as well as the northernmost record of this species. Furthermore, a listing of species of the family Dryopidae from Mexico and an identification key for the genera found in continental North America (Canada, EUA, and Mexico) are presented.